2010
DOI: 10.1007/s12098-010-0099-9
|View full text |Cite
|
Sign up to set email alerts
|

Staphylococcal sepsis presenting as pulmonary embolism

Abstract: Deep vein thrombosis in children is rare and is often secondary to a predisposing condition. Staphylococcal sepsis following furunculosis and complicated by deep vein thrombosis and septic pulmonary emboli in a fourteen-yr-old boy is presented. He was managed successfully with antibiotics and anticoagulation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…11 Aggressive treatment with appropriate antibiotics, anticoagulation, surgical drainage, and assisted ventilation, when indicated, are the cornerstones for treatment of this life-threatening triad of staphylococcal infection, DVT and septic emboli. 7,8 Antibiotics should be continued for 4-6 weeks as the DVT acts as a deep-seated source of infection. Screening for prothrombotic conditions is necessary to decide the duration of anticoagulation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…11 Aggressive treatment with appropriate antibiotics, anticoagulation, surgical drainage, and assisted ventilation, when indicated, are the cornerstones for treatment of this life-threatening triad of staphylococcal infection, DVT and septic emboli. 7,8 Antibiotics should be continued for 4-6 weeks as the DVT acts as a deep-seated source of infection. Screening for prothrombotic conditions is necessary to decide the duration of anticoagulation.…”
Section: Discussionmentioning
confidence: 99%
“…However, deep-vein thrombosis (DVT) has been reported infrequently [4][5][6] and association with septic pulmonary emboli in MSSA infections is rare. [5][6][7][8] Four successfully managed cases of invasive staphylococcal infection, all MSSA, presenting with DVT are presented.…”
Section: Introductionmentioning
confidence: 99%
“…Harris et al [10] reported bilateral renal vein thrombosis from pyelonephritis but due to a Klebsiella species. Staphylococcal bacteraemia is associated with venous as well as arterial thrombosis, in the absence of prothrombotic disorders [11]. Multiple mechanisms involved in interaction of SA with various body tissues, including native and undamaged heart valves, bones, joints, and other solid organs.…”
Section: Discussionmentioning
confidence: 99%
“…Though sepsis overall has been shown to increase the risk [9], studies have found a more pronounced association of gram positive bacterial infections, including Staphylococcus, with DVT [27]…”
Section: Tuberculosismentioning
confidence: 99%